THE EFFECT OF EMOTIONAL INTELLIGENCE ON THE PERFORMANCE OF EMPLOYEES - Soulaf Abdalqadir Hameed Alsady (Scholars Digest Publishing, 2024)
This research specialized in addressing the topic of the impact of emotional intelligence on the performance of employees, where the research problem crystallizes in identifying the role of emotional intelligence and its impact on the performance of employees. The research population is represented by (University of Maysan) and a group of (workers) was taken as a sample for the research, based on multiple statistical methods. For the purposes of this research, a simple random sample of workers at (University of Maysan) was selected as a means of applying the research, amounting to (200), which included a sample The study included managers and officials of the administrative divisions at the University of Maysan. (200) questionnaire forms were distributed to the working managers, and (184) questionnaires were retrieved, which means that the percentage of returned questionnaires amounted to approximately 95%, and this is a very high percentage.
Keywords: Emotional smartness, Employee performance, self-conscious, Quality of work performed, self-management.